The borderlands of culture : Américo Paredes and the transnational imaginary - Saldívar, Ramón (New Americanists., 2006)
The definitive life and work of Americo Paredes, the native South Texan poet, novelist, journalist, folklorist, ethnographer and first U.S. theorist of the border.